A Comparative Performance Study of the Matrix /sync Endpoint on Synapse and Tuwunel - Viana, Windson; Silva, Francisco Airton; Gomes, Francisco A. A.; Sales, Michel; Ivo, Roberto; Trinta, Fernando A. M.; Andrade, Rossana M. de C.; Macêdo, José A. F. de; Lagrota, Vinícius; Pacheco, Rodrigo; Rego, Paulo A. L. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Matrix is an open protocol for federated communication, primarily implemented by the Synapse server, with Tuwunel as an alternative. Client–server interaction relies on the synchronization (sync) mechanism, which delivers events and updates throughout the application lifecycle. This paper presents a controlled experimental comparison of Synapse and Tuwunel based on nearly 17,000 sync requests under increasing load and different filtering strategies. Results show that Tuwunel achieves lower response times in three of four configurations, but it does not yet support Simplified Sliding Sync (SSS) correctly. SSS on Synapse delivers the lowest latency across the evaluated settings. We also report saturation and resource trends under increasing load.